Natural abundance analysis of the role played by 15N as indicator for the certification of organic-system deriving food - Trapp, Talita (2022)
BACKGROUND: The natural abundance of stable isotope 15N (δ15N) in production systems has emerged as an alternative to distinguish organic products from conventional ones. This study evaluated the use of δ15N values recorded for nitrogen fertilizers, soil and plant tissue in order to set the differences between organic and conventional agricultural production systems applied to rice, potatoes, apple and banana crops. RESULTS: Values of δ15N recorded for N sources ranged from +5.58‰ to +18.27‰ and from −3.55‰ to +3.19‰ in organic and synthetic fertilizers, respectively. Values recorded for δ15N in food from organic rice, potatoes and banana farms were higher than values recorded for δ15N in conventional farms; the same was observed for values recorded for δ15N in leaves from the four crops. CONCLUSION: Results have allowed for differentiation between production systems due to values of δ15N recorded in leaves of all crops and food, for rice, potatoes and banana trees. © 2021 Society of Chemical Industry.